Sikap Saling Menghargai Antarmahasiswa melalui Kegiatan Kelompok Kecil Evangelisasi di Program Studi Pelayanan Pastoral - Jumilah, Bernadeta Sri; ., Wiwin; Leu, Helena Hay (SAPA - Jurnal Kateketik dan Pastoral, 2025)
Mutual respect is essential in fostering harmonious relationships among students, especially within diverse campus environments such as STP-IPI Malang Pastoral Ministry Study Program. This study aims to evaluate the effectiveness of small-group evangelization activities in enhancing mutual respect among students. An experimental method with a pretest-posttest control group design was utilized, involving two student groups: an experimental group (participating in evangelization activities) and a control group (not participating). Results showed a significant increase in mutual respect within the experimental group (pretest score 71.14 to posttest 129.05; p-value=1.27E-22), whereas the control group did not exhibit significant changes (pretest score 58.59 to posttest 63.36; p-value=0.127). The study concludes that small-group evangelization effectively enhances mutual respect among STP-IPI Malang students. Integrating these activities into the pastoral curriculum is recommended to strengthen students' social and spiritual character development.